Optimizing harvest stage and drying time to enhance yield and nutritive quality of whole-plant Tithonia diversifolia forage meal in arid tropics - Temoche Socola, Victor Alexander (2025)
Introduction: Tithonia diversifolia, also known as Mexican sunflower, is a tropical shrub with high forage potential, but limited information exists on the optimal harvest stage to balance yield and nutritional value. Methods: A 3 × 3 factorial design was implemented under tropical dry forest conditions in northern Peru, combining three regrowth stages (30, 45, and 60 days) with three plant fractions (leaf, stem, and leaf–stem mixture), with four replicates per treatment. Agronomic traits, dry matter yield, proximate composition, and in vitro dry matter digestibility (IVDMD) were evaluated. Results: Biomass yield increased significantly with harvest age, reaching 11.93 kg fresh weight and 3.45 kg dry matter per plant at 60 days, although with reduced nutritional quality due to a higher stem proportion. Leaves harvested at 30 days had the highest crude protein (16.5%) and soluble carbohydrates (48.2%) with the lowest crude fiber (19.3%). In contrast, the 45-day leaf samples achieved the highest IVDMD (62.34 ± 1.42%). A strong positive correlation was observed between leaf area and biomass yield (r = 0.93), and a moderate negative correlation with digestibility (r = –0.42). Discussion: Harvesting at 45 days provided the best compromise between biomass production and nutritional value. These findings highlight the potential of T. diversifolia as a strategic forage alternative for sustainable feeding systems in tropical dry environments.